Protecting Low Income Residents During Tax Increment Financing Redevelopment - Kristen Erickson (Washington University Journal of Law & Policy, 2011)
The Article focuses on the impact of tax increment financing (TIF) on low income residents in the U.S. Topics include urban development programs that use TIF, the U.S. Housing and Community Development Act of 1974, and the decrease in federal funding for urban redevelopment programs between 1974 and 2012.
Keywords: Tax increment financing; Urban renewal; Taxation – Law & amp; legislation; Poor – Taxation; Community development